PENGARUH INOVASI PRODUK DAN KEUNGGULAN BERSAING TERHADAP KINERJA USAHA PADA UMK DOMPET DI DUSUN GROGOLAN MOJOWARNO JOMBANG - Agustia, Yossi; Andayani, Sri; Pratiwi, Ni Made Ida (Research Journal of Social Science and Economics, 2025)
In this increasingly rapid business development and free trade, business actors/UMK compete in increasingly stringent business in various fields including the wallet industry. In anticipating this increasingly superior business competition, MSEs compete to create the products needed and fulfill market desires. The products created by MSEs are also diverse and not a few also have the same function, the same type and similar shape. This research was conducted with the aim of knowing the effect of product innovation and competitive advantage on business performance at UMK Wallet in Grogolan Mojowarno Hamlet, Jombang. This type of research uses quantitative research methods. The population in this study were all entrepreneurs or UMK owners whose number was known as 50 people. The sampling technique uses the census or random sampling method, so that the sample is no longer used because the population is the sample. This research was conducted by distributing questionnaires containing statements from indicators via Google form to all UMK Wallet in Grogolan Mojowarno Hamlet, Jombang. The data source for this research is primary data and secondary data. The data analysis technique used is the classical assumption test, multiple linear regression test and hypothesis testing. The results of the analysis of the data obtained show that Product Innovation and Competitive Advantage have a simultaneous or joint effect on Business Performance at UMK Wallet in Grogolan Mojowarno, Jombang.